Artikel Review : Polimer Tercetak Ion untuk Pemisahan Logam Tanah Jarang (Sintesis dan Karakterisasi): Review Article: Ion Imprinted Polymers for Separation of Rare Earth Metals (Synthesis and Characterization) - Putri, Syelena Prima; Pratomo, Uji; Fauziah, Retna Putri; Bahti, Husein Hernadi; Wyantuti, Santhy (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2024)
Rare earth metals (LTJ) are potential prospects that are widely applied in high technology such as cellphones, computer hard disks, solar cells, electric cars, musical instrument components, spacecraft manufacturing, defense industry. The use of REEs relies on their chemical, catalytic, electrical, magnetic and optical properties. In addition, the similar chemical and physical properties of rare earth metals make their separation very difficult and complicated, so appropriate and selective alternative separation methods are needed to obtain pure rare earth metals. One of the separation methods used is solid phase extraction using ion-imprinted polymer (IIP) adsorbents. IIP has the ability to adsorb with high selectivity because it stores the memory effect of the washed template ions. In this review article, an overview of various IIP syntheses for REE separation will be presented. It is hoped that this article can be a reference for research on IIP synthesis, especially for REEs. Keywords: Ion Imprinted Polymer, Rare Earth Metals (REEs), and IIP Synthesis Abstrak Logam tanah jarang (LTJ) merupakan prospek potensial yang banyak diaplikasikan pada teknologi tinggi seperti handphone, hard disk komputer, sel surya, mobil listrik, komponen perangkat alat musik, pembuatan pesawat luar angkasa industri pertahan. Penggunaan LTJ mengandalkan sifat kimia, katalitik, listrik, magnet, dan optiknya. Selain itu, sifat kimia dan fisika yang mirip pada logam tanah jarang membuat pemisahannya sangat sulit dan rumit, maka diperlukan metode pemisahan alternatif yang tepat serta selektif untuk mendapatkan logam tanah jarang yang murni. Salah satu metode pemisahan yang digunakan adalah ekstraksi fase padat menggunakan adsorben polimer tercetak ion (IIP). IIP memiliki kemampuan mengadsorpsi dengan selektivitas tinggi karena menyimpan memory effect dari ion template yang dicuci. Dalam artikel review ini, akan dipaparkan gambaran umum mengenai berbagai sintesis IIP untuk pemisahan LTJ. Artikel ini diharapkan dapat menjadi referensi untuk penelitian mengenai sintesis IIP terutama untuk LTJ. Kata Kunci: Polimer Tercetak Ion, Logam Tanah Jarang (LTJ) dan Sintesis IIP